A time-of-use pricing model of the electricity market considering system flexibility. (November 2022) - Wesseh, Presley K.; Lin, Boqiang
Abstract: This paper presents a time-of-use (TOU) pricing model of the electricity market that can capture the interaction between power plants, generation ramping, storage devices, electric vehicle loading, and electricity prices. Even though the model is calibrated to Chinese Fujian electricity market, it can be used to predict efficient equilibrium tariffs on any electricity system that seeks to emphasize the marginal costs principle for generators where consumer tariffs are regulated. We show that, for efficiency purposes, it is imperative for dynamic electricity pricing models to take into account technology-specific ramping parameters and various sources of power system flexibility. Also, by utilizing unused battery capacity, electric vehicles can significantly complement other storage devices to reduce power sector emissions and ensure grid stability. The model and results presented in this paper are useful to regulatory bodies in Fujian province for economic policy, and to the scientific community in terms of (i) offering a tool to promote more discussion on dynamic pricing in electricity markets, and (ii) enriching our understanding of how to design a TOU program in the light of flexible power resources.